Pierre-Olivier Méthot, dir. Philosophy, History and Biology: Essays in Honour of Jean Gayon - Bourrat, Pierrick (Philosophiques, 2025)
Pierre-Olivier Méthot, dir. Philosophy, History and Biology: Essays in Honour of Jean Gayon, Cham : Éditions Springer, 2023, 329 pages